1982
DOI: 10.1042/bj2060267
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the enzymic capacity for cysteine desulphhydration in liver and kidney of the rat

Abstract: The contribution of cystathionine gamma-lyase, cystathionine beta-synthase and cysteine aminotransferase coupled to 3-mercaptopyruvate sulphurtransferase to cysteine desulphhydration in rat liver and kidney was assessed with four different assay systems. Cystathionine gamma-lyase and cystathionine beta-synthase were active when homogenates were incubated with 280 mM-L-cysteine and 3 mM-pyridoxal 5'-phosphate at pH 7.8. Cysteine aminotransferase in combination with 3-mercaptopyruvate sulphurtransferase catalyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
492
2
14

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 673 publications
(513 citation statements)
references
References 35 publications
5
492
2
14
Order By: Relevance
“…Both cystathionine ␥-lyase and cystathionine ␤-synthase are expressed in the kidney (7,43). Following release, hydrogen sulfide can be stored in cells as bound sulfane sulfur that can be released by reducing conditions (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cystathionine ␥-lyase and cystathionine ␤-synthase are expressed in the kidney (7,43). Following release, hydrogen sulfide can be stored in cells as bound sulfane sulfur that can be released by reducing conditions (44).…”
Section: Discussionmentioning
confidence: 99%
“…The role of hydrogen sulfide in renal physiology and disease is beginning to be explored. Biochemical analysis has shown that the kidney produces hydrogen sulfide catalyzed by three enzymes: cystathionine ␥-lyase, cystathionine ␤-synthase, and 3-mercap-topyruvate sulfotransferase (7). Hydrogen sulfide content is decreased in the renal parenchyma in rats with streptozotocininduced diabetes, and administration of NaHS inhibited increases in TGF␤1, reactive oxygen species, and type IV collagen in diabetic rats (8).…”
mentioning
confidence: 99%
“…The role of H 2 S in inflammation is suggested by several studies (8 -11); however, the underlying mechanism is unknown. Remarkably, H 2 S can also induce a state of suspended animation in mice by decreasing the metabolic rate and the core body temperature presumably by inhibiting cytochrome c oxidase in the respiratory chain (12).Endogenous H 2 S is presumed to be generated primarily by desulfhydration of cysteine catalyzed by the two pyridoxal phosphate (PLP) 3 -dependent enzymes in the transsulfuration pathway: cystathionine ␤-synthase (CBS) and cystathionine ␥-lyase (CSE) (13,14). In fact, it is widely assumed, based on the reported absences of CSE in the brain (15) and of H 2 S in the brain of CBS knock-out mice (16), that CBS is the primary source of H 2 S in this organ, whereas CSE plays the equivalent role in the peripheral vasculature (3).…”
mentioning
confidence: 99%
“…31 This implies that H 2 S deficiency might be related to pulmonary vasoconstriction and intimal thickening which are pathological factors associated with pulmonary hypertension. 11 In rats, the NOS inhibitor L-NAME produced a time-dependent elevation in systolic blood pressure associated with inhibition of CSE gene expression and H 2 S production whereas exogenous H 2 S administration prevented the development of hypertension induced by L-NAME. 32 There is also the possibility that excessive levels of H 2 S could contribute to hypotension associated with either sepsis or endotoxemia.…”
Section: General Physiology Of H 2 S In the Cardiovascular Systemmentioning
confidence: 98%